The Effect of Extracellular Superoxide Dismutase (SOD3) Gene in Lung Cancer - Zhang, Yundi; Lu, Xuan; Zhang, Yueyang; Zhao, Dongbo; Gong, Haoming; Du, Yuxin; Sun, Hua (Frontiers in Oncology, 2022)
Background: The recognition of new diagnostic and prognostic biological markers for lung cancer, the most severe malignant tumor, is an essential and eager study. In a microenvironment, superoxide dismutase 3 (SOD3) can adjust active oxygen, and it refers to a secreted antioxidant enzyme. It was also found to be cancer-related, and in lung cancer, it was remarkably down-regulated. More and more new cancer research focuses on the function of SOD3. Despite this, there is no good description of SOD3 function in the LC progression. Methods: Through bioinformatics analysis, we found that SOD3 was a possible novel lung cancer gene in this study. We analyzed data sets from Gene Expression Comprehensive Database (GEO) and the Cancer Genome Atlas (TCGA), and SOD3 expression was studied in lung cancer. This study estimated the SOD3 diagnosis and prognosis through gene expression differential display, gene set enrichment analysis (GSEA), enrichment and genomes (KEGG) analysis, and gene ontology (GO). Then in order to investigate the SOD3 presentation in lung cancer cells, we used Western Blot and also applied Flow cytometry to detect the impact of anti-tumor medicine on tumor cell apoptosis. Results: We found that the expression level of SOD3 in lung cancer was low (P = 4.218E-29), while the survival of lung cancer patients with high SOD3 expression was shorter (LUSC p =0.00086，LUAD p=0.00038). According to the result of western blot, the expression of SOD3 in tumor cells was higher than that in normal cells. The ratio of early apoptosis induced by anti-cancer drugs was 10.5% in normal cells, 35.1% in squamous cell carcinoma and 36.9% in adenocarcinoma.The SOD3 high expression was associated with poor survival probability by multivariate analysis (HR: 1.006, 95% CI 1.002–1.011, p=0.006). Moreover, SOD3 high expression group had higher ESTIMATE scores,and larger amount of immune infiltriting cells. SOD3 expression is correlated with PDCD1 and CTLA4 expression. Conclusions:SOD3 gene can be used as a prognostic gene in lung cancer patients, and lung cancer patients with high expression of this gene can reap worse prognostic outcome. It can be used as a new clinical method and prognosticator for lung cancer patients.